Impacts of environmental parameters on the foraging behaviour and breeding success of southern elephant seals from Kerguelen Islands : influence of individual strategies and inter-annual variability - Mestre, Julie (HAL CCSD, 2020)
Because time-series relative to foraging ecology, environmental parameters and population trends are scarce, few studies focused on the mechanisms linking oceanographic variables with the foraging behaviour and breeding success in marine top predators. This PhD thesis aims to assess the effects of inter-annual environmental conditions and individual strategies on the foraging ecology and breeding success of the southern elephant seal (Mirounga leonina), a key species of the Southern Ocean. The simultaneous analysis of stable isotopes and tracking-diving time-series highlighted that the foraging habitats, as well as the diving- and foraging behaviour of female seals, remained stable over the last fourteen years. This thesis also revealed a consistency in the Antarctic and sub-Antarctic foraging strategies, and a decrease in the body condition of females exploiting the latter habitat. The weaning mass of their pups, considered as a proxy of the breeding success, decreased too. A difference in habitat quality was detected between the area located east and west of the Kerguelen archipelago, with the area located west providing a higher foraging success. Moreover, a spatial structuration of foraging strategies was highlighted between two breeding sites located at Kerguelen Island. Despite consistency in the behaviour of seals, an overall increase in body condition was assessed over the study period. Combined with a global decrease in δ13C values, this result suggests that some modifications are occurring in the food web of the Southern Ocean. En raison du manque de séries temporelles associant écologie en mer, paramètres océanographiques, et trajectoires démographiques, peu d’études se sont intéressées aux mécanismes reliant conditions océanographiques, succès alimentaire à l’échelle des trajets en mer, et succès reproducteur associé chez des prédateurs marins. Le présent travail de thèse propose de déterminer l’effet de la variabilité interannuelle des paramètres environnementaux, ainsi que des stratégies ...